Comprehensive Study Enhancing Quality Of Education In Indonesia: Leadership, Work Environment, Motivation Among Vocational School Teachers - Dwiyono, Gunawan; Purnomo, Purnomo; Sutadji, Eddy; Devi, Mazarina (International Journal of Educational Research & Social Sciences, 2023)
The Covid-19 pandemic's end led to rapid adaptation in the education sector with a shift to online learning for approximately 2 years. This prolonged duration resulted in a decline in education quality evident in online learning. Post-pandemic research aims to analyze the impact of leadership, work environment, and work motivation on vocational teachers in Indonesia. Regression analysis demonstrates that these factors collectively influence education quality. However, partial analysis reveals insignificant effects of leadership, while the work environment significantly impacts education quality. Motivation and teacher performance show no significant contributions to education quality. Further research recommendation includes using longitudinal analysis over an extended period to assess variable-related changes.